SyncSmartv: framework para sincronização de aplicações smart TV com programas televisivos - Nsimba, Cedrick Bamba (2015)
Smart TV applications are typically disconnected from the content of the tuned programming on the TV set. Some broadcasters offer specific applications for programs, however, these applications are generally just loosely coupled or synchronized to the program. Furthermore, applications are fully under domain of broadcasters, that have the information about the transmitted content. Based on the fact that synchronized information may arise from third-parties, obtained by local content processing or offered directly by the viewers, new opportunities will be opened up for developing a bunch of new interesting applications aiming to promote the user interaction level in TV. Moreover, it will have new user interaction possibilities while using mobile devices and computers, furthermore a new business model will be emerged. In this master thesis, the SyncSmartv framework is presented and evaluated. The aforementioned framework offers several APIs that facilitate the development of Smart TV applications synchronized with TV program contents. The aim is to provide some facilities for developers to implement applications in this area in a clear approach without being concerned about low-level implementation details.